Comparative Mitochondrial Genomic Analysis Robustly Supported That Cat Tapeworm Hydatigera taeniaeformis (Platyhelminthes: Cestoda) Represents a Species Complex - Wang, Hui-Mei; Li, Rong; Deng, Yuan-Ping; Liu, Guo-Hua; Fu, Yi-Tian (Frontiers in Veterinary Science, 2022)
Hydatigera taeniaeformis is one of the most common intestinal tapeworms that has a worldwide distribution. In this study, we sequenced the complete mitochondrial (mt) genome of H. taeniaeformis from the leopard cat (designated HTLC) and compared it with those of H. taeniaeformis from the cat in China (designated HTCC) and Germany (designated HTCG). The complete mt genome sequence of HTLC is 13,814 bp in size, which is 167 bp longer than that of HTCC, and is 74 bp longer than that of HTCG. Across the entire mt genome (except for the two non-coding regions), the sequence difference was 3.3% between HTLC and HTCC, 12.0% between HTLC and HTCG, and 12.1% between HTCC and HTCG. The difference across both nucleotide and amino acid sequences of the 12 protein-coding genes was 4.1% and 2.3% between the HTLC and HTCC, 13.3% and 10.0% between the HTLC and HTCG, and 13.8% and 10.6% between the HTCC and HTCG, respectively. Phylogenetic analysis based on concatenated amino acid sequences of 12 protein-coding genes showed the separation of H. taeniaeformis from different hosts and geographical regions into two distinct clades. Taken together, our analysis showed that the cat tapeworm H. taeniaeformis represents a species complex. The novel mt genomic datasets provide useful markers for further studies of the taxonomy and systematics of cat tapeworm H. taeniaeformis.